Effect of 4-AP on MPP+/ MPTP-induced Parkinson's disease model: Effect of 4-AP on Parkinson's disease - Rong, Qiongwen; Zhou, Chang; Ma, Yuanyuan (Cellular and Molecular Biology, 2023)
To study the effect of 4-AP on Parkinson's disease (PD) cells and animal model. PD cells were pretreated with different concentrations of 4-AP for 24 hours, then PD cells were prepared by MPP+, and the cell activity was detected by CCK8 kit. PD mice were prepared by MPTP and then given 4-AP for 10 days. Finally, the behavioral changes of mice were detected by pole climbing test and open field test, and the expression of TH in the midbrain was detected by IHC and WB. 4-AP could increase the activity of PD cells induced by MPP+. In the field experiment, the total spontaneous activity distance of PD mice (1380.01 ± 151.84) cm was not different from that of 4-AP intervention (1228.65 ± 358.25) cm but was reduced than that of normal mice (2121.89 ± 235.95) (P<0.05). In the pole climbing test, the pole climbing time of PD mice was (7.95 ± 1.02) seconds, compared with that of PD mice treated with 4-AP, there was no difference between the two groups, but it was reduced than that of normal mice (P<0.05). IHC and Western blot showed that the mesencephalic TH of PD mice and drug-treated mice were reduced than that of normal mice (P<0.05), however, drug intervention could not reduce the expression of TH in mice with PD (P>0.5). 4-AP pretreatment can reduce the toxic and side effects of MPP+. 4-AP can not improve the motor function impairment of PD mice, nor can it reduce the toxic effect of MPTP on dopaminergic neurons. There are differences between pre-treatment and post-intervention in the treatment of MPP+/MPTP-induced PD. In order to better explore the drug treatment and target of PD, it is hoped that a cure for PD can be found in PD animals. The timing of intervention and cell and animal experiments should complement each other.